CHARACTERISTICS OF PROBIOTIC KOUMISS FROM GOAT MILK WITH ADDITION OF ROSELLE EXTRACT (Hibiscus Sabdariffa Linn) - Nuraeni, E.; Arief, I.I.; Soenarno, M.S. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
Goat milk and roselle (Hibiscus sabdariffa Linn) are food ingredients with health functionalproperties. This research used Lactobacillus acidophilus RRAM-01 and Lactococcus lactis RRAM-01which had been proven as probiotic, and Saccharomyces cereviceae. Saccharomyces cereviseae wasused to produce specific flavor components in koumiss (bacterial fermentation product). The objectiveof this research was to study the characteristics of goat milk probiotic koumiss added that with roselleextract. The results showed that the addition of different concentration of roselle extract (0%, 0.5%, and1%) in the goat milk probiotic koumiss had no effect on chemical and microbiological characteristics ofkoumiss. Goat milk processed into koumiss had ability to suppress the growth of coliform and hadstrong inhibition activity against Escherichia coli ATCC 25922 as tested by agar diffusion test.Microbiological analysis used in this research was the pour plate method. Population of lactic acidbacteria indicated that the product fulfilled standards as probiotics koumiss (1011 cfu/mL), coliform wasnot detected in the products, therefore the products met the criteria of The National Agency of Drug andFood Control (NA-DFC) as probiotic functional food. Sensory evaluation was conducted by usinghedonic quality test. Based on the hedonic quality test, addition of different concentrations of roselleextract increased the intensity of red color and koumiss viscosity, but had no effect to the aroma andsourness of koumiss.